Hybrid evolutionary meta-optimization assisted by recurrent neural networks for interpretable parametric symbolic models - Flavio Adalberto Gomes; Wanderson Rainer H. Araujo; Marcio R. Cunha Reis; Geovanne Pereira Furriel; Guilherme Alberto S. Ribeiro; Viviane M. Gomes Pacheco; Marcella Scoczynski R. Martins; Clóves Gonçalves Rodrigues; Antonio Paulo Coimbra; Wesley Pacheco Calixto (Swarm and Evolutionary Computation, 2026)

Comments on Acosta-Velázquez et al. changes in mangrove coverage classification criteria could impact the conservation of mangroves in Mexico. Land Use Policy, 2023, 129, 106651 - Carlos H. Troche-Souza; Samuel Velázquez-Salazar; María Isabel Cruz-López; María Teresa Rodríguez-Zúñiga; José Alberto Alcántara-Maya; Berenice Vázquez-Balderas; Luis Valderrama-Landeros; Edgar Villeda-Chávez; Rainer Ressl (Land Use Policy, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Ageusia and anosmia, a common sign of COVID-19? A case series from four countries - Jair Vargas-Gandica; Daniel Winter; Rainer Schnippe; Andrea G. Rodriguez-Morales; Johana Mondragon; Juan Pablo Escalera-Antezana; María del Pilar Trelles-Thorne; D. Katterine Bonilla-Aldana; Alfonso J. Rodriguez-Morales; Alberto Paniz-Mondolfi (Journal of NeuroVirology, 2020)

Kapazitätssteigerung bei einer Wasserkraftanlage durch Unterdruckbetrieb - Praxiserfahrungen - Rainer Verdino; Josef Klatzer-Hoffmann; Boris Huber; Freddy Alberto Florez (WASSERWIRTSCHAFT, 2019)

Kapazitätssteigerung bei einer Wasserkraftanlage durch Unterdruckbetrieb - Modellversuche - Boris Huber; Freddy Alberto Florez; Rainer Verdino; Josef Klatzer-Hoffmann (WASSERWIRTSCHAFT, 2019)

Opposite fates of the purine metabolite allantoin under water and nitrogen limitations in bread wheat - Alberto Casartelli; Vanessa J. Melino; Ute Baumann; Matteo Riboni; Radoslaw Suchecki; Nirupama S. Jayasinghe; Himasha Mendis; Mutsumi Watanabe; Alexander Erban; Ellen Zuther; Rainer Hoefgen; Ute Roessner; et al. (Plant Molecular Biology, 2019)

Load-Adaptive Scaffold Architecturing: A Bioinspired Approach to the Design of Porous Additively Manufactured Scaffolds with Optimized Mechanical Properties - Alberto Rainer; Sara M. Giannitelli; Dino Accoto; Stefano De Porcellinis; Eugenio Guglielmelli; Marcella Trombetta (Annals of Biomedical Engineering, 2012)

Electrospun Hydroxyapatite-Functionalized PLLA Scaffold: Potential Applications in Sternal Bone Healing - Alberto Rainer; Cristiano Spadaccio; Pietro Sedati; Federico De Marco; Simone Carotti; Mario Lusini; Gianluca Vadalà; Alberto Di Martino; Sergio Morini; Massimo Chello; Elvio Covino; Vincenzo Denaro; et al. (Annals of Biomedical Engineering, 2011)

Poly-l-Lactic Acid/Hydroxyapatite Electrospun Nanocomposites Induce Chondrogenic Differentiation of Human MSC - Cristiano Spadaccio; Alberto Rainer; Marcella Trombetta; Gianluca Vadalá; Massimo Chello; Elvio Covino; Vincenzo Denaro; Yoshiya Toyoda; Jorge A. Genovese (Annals of Biomedical Engineering, 2009)